The Dilemma of Surgical Timing in Acute Aortic Valve Endocarditis: Does Early Surgery Improve Risks or Prognosis? - Michele D’Alonzo; Lorenzo Di Bacco; Antonio Fiore; Massimo Baudo; Francesca Zanin; Chiara Baldelli; Cyrus Moini; Thierry Folliguet; Claudio Muneretto (Journal of Cardiovascular Development and Disease)
Background: Acute aortic valve infective endocarditis (IE) presents a critical surgical timing dilemma. This study investigates whether early surgical intervention (within seven days of targeted antibiotic therapy initiation) affects mortality and clinical outcomes compared to delayed/conventional surgery. Methods: A retrospective, multicenter analysis of 204 patients with aortic IE was conducted, excluding emergency cases requiring immediate intervention. Patients were stratified into EARLY (≤7 days) and LATE (>7 days) surgical groups. Primary endpoints included in-hospital mortality and major adverse events, while secondary endpoints assessed long-term survival, recurrence, and reintervention rates. Results: No significant differences in in-hospital mortality were observed between groups (16% in both). The LATE group exhibited a trend toward increased permanent pacemaker implantation (16% vs. 8.2%; p = 0.100) and a higher incidence of postoperative atrial fibrillation (36% vs. 24%, p = 0.048). Infective endocarditis recurrence and long-term survival did not significantly differ between groups. Predictors of one-year mortality included chronic kidney disease, annular abscess, extracorporeal membrane oxygenation (ECMO) use, and prolonged mechanical ventilation. Conclusions: These findings suggest that early surgery, following a short course of antibiotics, does not compromise outcomes nor increase recurrence risk, challenging the conventional preference for delayed intervention in non-emergency IE cases.